INTRAOPERATIVE AND POSTOPERATIVE COMPLICATIONS IN PHACOVITRECTOMY FOR EPIRETINAL MEMBRANE AND MACULAR HOLE: A Clinical Audit of 1, 000 Consecutive Eyes. Issue 9 (September 2018) - Fajgenbaum, Mark A. P.; Neffendorf, James E.; Wong, Roger S.; Laidlaw, David A. H.; Williamson, Tom H.
Abstract : Purpose: The aim of this study was to report the intraoperative and postoperative complications of phacovitrectomy for epiretinal membrane (ERM) and macular hole (MH). Methods: This was a retrospective audit of 1, 052 phacovitrectomy operations (410 for ERM and 642 for MH) by the same surgical team between 1998 and 2017. Outcome measures included rates of intraoperative anterior segment and posterior segment complications such as posterior capsule rupture and retinal breaks. A subgroup analysis of 189 procedures in which postoperative complications were rigorously recorded was also undertaken. Results: The rate of posterior capsule rupture was 2.2%, with no difference between ERM and MH (1.7 vs. 2.5%; P = 0.40). Iatrogenic retinal tears were more common in MH than in ERM surgery (15.6 vs. 6.8%; P < 0.001). The chance of one or more anterior segment or posterior segment intraoperative complications occurring (excluding iatrogenic retinal breaks) was not associated with: indication for surgery, grade of surgeon, gauge of surgery, surgical machine, diabetic status, patient sex, or patient age. Subgroup analysis showed postoperative events as follows: posterior capsular opacification 10.6% (20/189), posterior synechiae 4.2% (8/189), uveitis 2.1% (4/189), angle closure glaucoma 1.6% (3/189), and rhegmatogenous retinal detachment 1.1% (2/189). Conclusion: Phacovitrectomy seems to be safe in phakic patients with ERM or MH, performed either by fellows or consultants. It avoids the requirement for repeat surgery and is more cost and resource efficient. Abstract : An audit of the intraoperative complications of phacovitrectomy for epiretinal membrane and macular hole was performed on more than one thousand consecutive eyes. A subgroup analysis of postoperative complications is also reported. Phacovitrectomy seems to be a safe management option for epiretinal membrane or macular hole.